Metaphors of Pain and Memory in the Lyrics of “All Too Well” by Taylor Swift - Sheilita Saputri; Otong Setiawan Djauhari (Jurnal Pustaka Cendekia Pendidikan, 2025)
This study explores the metaphorical representation of pain and memory in Taylor Swift’s song All Too Well, a work widely regarded as an emotionally intense lyrical narrative. The objective of the study is to examine how Swift utilizes figurative language—particularly metaphor—to convey themes of emotional trauma and recollection within the context of a failed romantic relationship. Using a qualitative descriptive approach, this study employs close reading and metaphor analysis based on Conceptual Metaphor Theory (Lakoff & Johnson, 1980). The findings reveal that Swift constructs a poetic narrative built upon eight primary metaphors that transform abstract feelings into vivid, sensory imagery. These metaphors not only shape the listener’s emotional perception but also function as narrative devices that give structure to the song’s temporal shifts and emotional progression. The significance of these results lies in their illustration of how contemporary song lyrics serve as a medium for literary expression and emotional articulation. In conclusion, All Too Well exemplifies the function of metaphor in mediating personal trauma through artful linguistic choices that resonate with collective human experience.